TANTANGAN IMPLEMENTASI CIRCULAR ECONOMY DALAM PENGELOLAAN SAMPAH PERKOTAAN (STUDI KASUS: KOTA DENPASAR) - Sutrisna Wijaya Putra, A.A. Gde; Mahendra Dewi, Ni Luh Putu; Maharani, Shinta Enggar (Jurnal Ecocentrism, 2025)
The transformation of waste management toward a circular economy has become a crucial agenda for urban sustainability in Indonesia, including Denpasar, the economic and tourism hub of Bali. This study aims to analyze the challenges in implementing a circular economy within Denpasar’s urban waste management system using descriptive-analytical approach based on secondary data from 2024. The findings indicate that although Denpasar has established a strong regulatory framework through Regional Regulation No. 3 of 2015 and Mayor Regulation No. 50 of 2018, its implementation still faces several structural constraints. According to data from the Denpasar Environmental and Sanitation Agency (DLHK) up to 2024, assessed at only 67%, the informal sector remained inactive (0%), and budget allocation waste management was relatively low (1.8% of the total city budget). Technically, the Denpasar DLHK Performance Report and several local media sources confirm that the Sarbagita Suwung Regional Landfill (32.4 ha) has exceeded its technical capacity. Limited public participation in waste segregation and weak cross-sectoral collaboration further hinder the realization of circularity. To achieve an environmentally resilient city, Denpasar needs to strengthen institutional collaboration, develop green financing Tri Hita Karana.